POETICS OF THE “SUBLIME” IN THE POETRY OF JURGIS BALTRUŠΑΙΤΙS - Снежко, Юлия (Literatūra, 2013)
Although many aspects of J. Baltrušaitis’ works (e.g., themes of transcendence, eternity, infinity and mystery) are directly or indirectly related to the problematics of the sublime, various researchers analyzing his texts haven’t problematized it yet. In this article, it is shown that it is present both in Baltrušaitis’ ideas of aesthetics and his poetry in Russian and Lithuanian languages. The poetics of the sublime here is mainly analyzed through the topos of silence. The author distinguishes two types of the sublime in his poetry: the “empty sublime” (its element of “bad infinity” makes part of the “diabolical” paradigm peculiar to early Russian symbolists), expressed in quite a small number of his poems in Russian, and the religious one – in the broad sense – that has a special meaning in all his poetry and, on the one hand, is articulated through the rhetoric of moral duty, thus approaching the mode of the tragic, and, on the other hand, it is disclosed through the prayerful feeling of “the miracle of being”, thus drawing nearer the paradigm of beauty.